Acute electroencephalography responses during incremental exercise in those with mental illness - Robertson, C. V.; Skein, M.; Wingfield, G.; Hunter, J. R.; Miller, T. D.; Hartmann, T. E. (Frontiers in Psychiatry, 2023)
Introduction: Depression is a mental illness characterized by a process of behavioral withdrawal whereby people experience symptoms including sadness, anhedonia, demotivation, sleep and appetite change and cognitive disturbances. Frontal alpha asymmetry differs in depressive populations and may signify affective responses, with left frontal alpha asymmetry corresponding to such aversive or withdrawal type behavior. On an acute basis, exercise is known to positively alter affect and improve depressive symptoms and this has been measured in conjunction with left frontal alpha asymmetry as a post exercise measure. However, the EEG responses during exercise in those with mental illness has not yet been elucidated. Furthermore, it It is not yet known if these affective EEG responses to exercise occur during exercise or only after completion of an exercise bout. This study therefore aimed to measure EEG responses during exercise in those with mental illness. Materials and methods: Thirty one participants were allocated into one of two groups; those undergoing management of a mental health disorder (MI; N=19); or reporting as apparently healthy (AH; N=12). EEG responses at rest and during moderate incremental exercise were measured at the PFC and the motor cortex. EEG data at prefrontal cortexPFC left side (F3, F7, FP1), prefrontal cortexPFC right side (F4, F8, FP2) and motor cortex (C3, Cz and C4) were analyzed in line with oxygen uptake at rest, 50% of ventilatory threshold (50% VT) and at VT. Results: EEG responses increased with exercise across intensity from rest to 50% VT and to VT in all bandwidths (P<0.05) for both groups. There were no significant differences in alpha activity responses between groups. Gamma responses in the PFC were significantly higher in MI on the left side compared to AH (P<0.05). Conclusion: Alpha activity responses were no different between groups at rest or any exercise intensity. Therefore the alpha activity response previously shown post exercise was not found during exercise. However, The increased in PFC gamma activity in the MI group compared to AH adds to the body of evidence showing increased gamma can differentiate between those with and without mental illness.